"Indian Ballerinas Toe Up": Maria Tallchief and Making Ballet "American" in the Tribal Termination Era. (18th September 2014) - Kowal, Rebekah J.
Abstract : Ballet faced formidable obstacles in establishing itself as a "home-grown" transplant at mid-century. Scholars have emphasized choreographic efforts to cultivate a nationally identifiable style during the period, focusing primarily on the emergence of Balanchine and neo-classicism. Yet the role of dancers in the Americanization of ballet largely has not been probed. This article examines the part that Maria Tallchief, daughter of a "full-blooded" Osage Indian father and Scotch-Irish mother, and the first American ballerina to reach prima status, played in changing public perceptions of ballet in the mid-twentieth century. Between 1952 and 1954, national magazines such as Dance magazine, Holiday, and Newsweek featured images of Tallchief on their covers, lending visual credibility to claims that ballet, which many at the time considered a "foreign" dance form, had come of age in the U.S. I argue that iconographic portrayals of Tallchief's face, legs, and feet, which illustrated the dancer's physical assimilation of Balanchine's approach to dance technique, along with narratives of her personal story, advanced an account of ballet's Americanization that placed the dancer, as much as if not more than Balanchine, at center stage. I then illuminate how Tallchief's exemplification of self-discipline and initiative bolstered nostalgic arguments about the successful "citizenship" of white ethnic immigrants, while also promoting arguments about the viability of Indian assimilation during the tribal termination era. When seen in the contemporaneous contexts of ballet's Americanization and societal debates over Native American citizenship, Tallchief's story is seen to complicate the meanings of "assimilation" and "citizenship" in postwar America.